Clinical, Haemodynamic, Rheological, and Biochemical Findings in 126 Patients with Intermittent Claudication. Issue 5892 (8th December 1973) - Dormandy, J. A.; Hoare, E.; Colley, J.; Arrowsmith, D. E.; Dormandy, T. L.
Abstract : Increased blood viscosity has been shown to be an important factor in reducing blood flow in a review and analysis of the history, clinical findings, and haemodynamic, rheological, radiological, and biochemical measurements in 126 patients with intermittent claudication. In some patients increased viscosity seemed to be the determining cause of claudication. A raised plasma fibrinogen was the most common single biochemical abnormality. The results of conventional serum lipid and lipoprotein estimations were abnormal in the series as a whole but did not correlate with clinical findings or flow measurements at individual patient level. There was, however, a significant correlation between some clinical findings and the susceptibility of the red cells to autoxidation.